2016
DOI: 10.1364/boe.7.004660
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral blood flow is decoupled from blood pressure and linked to EEG bursting after resuscitation from cardiac arrest

Abstract: Abstract:In the present study, we have developed a multi-modal instrument that combines laser speckle imaging, arterial blood pressure, and electroencephalography (EEG) to quantitatively assess cerebral blood flow (CBF), mean arterial pressure (MAP), and brain electrophysiology before, during, and after asphyxial cardiac arrest (CA) and resuscitation. Using the acquired data, we quantified the time and magnitude of the CBF hyperemic peak and stabilized hypoperfusion after resuscitation. Furthermore, we assesse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 30 publications
1
38
0
Order By: Relevance
“…The animal model of ACA and resuscitation employed in this study has been described previously [41][42][43][44]48 and is summarized in Fig. 1.…”
Section: Preclinical Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…The animal model of ACA and resuscitation employed in this study has been described previously [41][42][43][44]48 and is summarized in Fig. 1.…”
Section: Preclinical Modelmentioning
confidence: 99%
“…LSI is an established technique to measure blood flow in preclinical models and humans, [50][51][52] including CA studies. 44,53,54 SFDI is an established technique 55,56 that enables separate quantification of the diffuse optical absorption and scattering coefficients of tissue. The absorption coefficient, when measured at multiple nearinfrared wavelengths, provides information regarding concentrations of oxygenated and deoxygenated hemoglobin (ctHbO2, ctHb, respectively) in tissue.…”
Section: Optical Imagingmentioning
confidence: 99%
See 1 more Smart Citation
“…Ten male Wistar rats (weight ~300-400 g) were imaged for this study, and the animal preparation procedures are described in our previous publications [7,8,13,14]. Before the experiment, all rats were endotracheally intubated under isoflurane anesthesia.…”
Section: Animal Preparationmentioning
confidence: 99%
“…Recently, we demonstrated that the combination of Spatial Frequency Domain Imaging (SFDI) and Laser Speckle Imaging (LSI)) can quantify tissue metabolic changes with high spatial and temporal resolution [6]. We also recently applied high-speed LSI [7] and SFDI [8] to measure perfusion, oxygenation, and tissue scattering in the brain in a cardiac arrest (CA) model of global cerebral ischemia. The capability of our rapid multimodal SFDI+LSI system to image blood flow and hemoglobin concentration simultaneously enables high-speed measurement of CMRO 2 [9].…”
Section: Introductionmentioning
confidence: 99%